Differentiated impact of social and non-social content in Alexithymia: A facial thermal infrared imaging study - Lucas De Zorzi; Eduardo S. Martínez-Velázquez; Jacques Honoré; Henrique Sequeira (PLoS ONE, 2026)
Alexithymia, a difficulty in processing and expressing emotions, is associated with socio-emotional challenges and altered autonomic responses. This raises the question of whether cognitive (CA) and affective (AA) alexithymia can be differentiated based on parasympathetic and sympathetic indices. This study explores the reactivity of CA and AA individuals to social and non-social emotional stimuli. Participants, categorized as non-alexithymic (NA), CA, or AA based on the Toronto Alexithymia Scale and Bermond-Vorst Alexithymia Questionnaire, completed assessments on empathy, social phobia, depression, and anxiety. They viewed images from the International Affective Picture System (IAPS), varying in emotional (unpleasant, neutral, and pleasant) and social (with humans, without humans) content, and evaluated them at the end of the experiment. Heart rate variability (HRV) and facial infrared thermal imaging (fITI) were recorded during image presentation. Psychometric analysis revealed higher social phobia avoidance and depression scores in CA compared to AA, and higher trait anxiety in CA compared to both AA and NA. CA and NA participants scored higher on empathic personal distress than AA. At the autonomic level, NA participants exhibited increased HF-HRV and decreased LF-HRV in response to emotional social stimuli, whereas CA and AA groups displayed no HRV modulation. Thermal responses revealed decreased nose temperature for non-social stimuli in CA, while AA showed the opposite pattern. HRV and fITI measures highlight distinct autonomic reactivity to socio-emotional stimulation and thus effectively differentiate cognitive and affective alexithymia. These physiological findings reinforce the psychometric distinction between CA and AA, suggesting tailored interventions for alexithymic disorders.